Dimensi sosial keagamaan dalam Keluarga Permana: analisis semiotik = Sociotic Dimension in "Keluarga Permana": a semiotic analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
This research aims to reveal the meaning of social religious dimension in semiotic point of view in work of Ramadhan K.H.-Keluarga Perrnana(Kr To comprehend and to reveal the social religious dimen- sion of the KP needs to use intertextual approach. Thus, there are two approaches used in this research, they are semiotic and intertextual. Correspond to the objective of this research, the qualitative method is imployed in this research. The social religious dimension is viewed as a sign placed on the frame of literary communication system. The social religous dmension of the KP occurs in literary communication among the author, the reader, and the universe. The meaning reli ng of social reli gious dimension is the change of - gion which results in social conflict in the society, because ithurts the religious feeling of the community. It will be more hurting when the change of religion is considered tote strange by the society, such as the change of religion through marriage with oppression of the bride by the bride groom. The condition can ruin the harmony of life among the reli ous people, even it can ruin the unity of the nation. In the case of such changeof religion, the convey of a religion to religious people existed, this aairist the law. -Religion as the principle of life to gain happiness is another significant idea. This idea includes iman (belief) as self control, the role of religion in the family life to build the children behavior, extra merital sexual intercourse and abortion as the indicator of religious moral erosion. Other idea functions the background is the belief crisis as the source of the social problem. The implication of this idea is the existence of the corruption crime, power abuse, disharmony of the family life, moral decadency and forced marriage in modem 'version'. This is due to the belief crisis in the society, though social and economical factor can be the reason for the above phenomena.